Challenging future practice possibilities - Higgs, Joy; Cork, Steven; Horsfall, Debbie (Practice futures ;, 2019)
What might the futures of practice be like?" is far from a straightforward question. Emphasising "the" before the word future, implies one future. But futures thinkers have identified a range of futures that people think about. In this book we reflect on possible, probable, and preferable futures in relation to practice and work. Readers are invited to consider how their own engagement in shaping possible futures will support ways of working that they deem preferable, even those they can hardly imagine. 'Challenging Future Practice Possibilities' also examines influences that are maintaining the status quo and others that are pushing interest-driven change. Authors consider the major challenges that practice and practitioners face today such as wicked problems, fears for the future and complex demands and opportunities posed by the digital revolution. A number of examples of future-oriented work directions such as protean careers and artificial intelligence enhancing or even replacing human workforces, are considered along with concerns like the vulnerability of many work situations and workers. In some cases workers and employers alike are unprepared for these challenges, while others see adapting to these situations as yet another pathway of practice futures evolution.